The free coinage of silver - Carnell, Fannie (My University, 1897)
Introduction: It is important to understand clearly and exactly what the free coinage of silver under present conditions means. It is the right of anyone to deposit silver at the limited State’s mint and have every 3711/4 grains of pure silver stamped free of charge, One Dollar, which dollar shall be full legal tender at its face value in payment of debts and obligations of all kinds, public and private in the United States. Why do we need this free and unlimited coinage of silver? Is it going to benefit the American people? If so, how? Let us first consider how it will benefit the West. There are a great many reasons peculiar to its resources and environment which justify the desire of the west for free silver. The term “The West” comprises by far the vaster portion of the union, tuning with unbounded natural resources, and occupied by millions of enterprising and industrious peoples. Conceded to be the granary of the world, it is at once the metallic treasure house of the nation and the principal source of food supply. Its annual yield of grain, livestock, wool, and metals, is far in excess of two billion dollars. It furnishes the great lines of transportation with the bulk of their business and equips our manufactories with much of the raw material essential to their continued exploration.
Citation: Carnell, Fannie. The free coinage of silver. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Coinage; Silver; Manufacture; Inflation; Mint; Economics; Theses; Manuscripts (documents)